The Communication Strategy of the Ministry of Religious Affairs in Tebing Tinggi for the Prevention of Early Marriage in Padang Hulu Subdistrict - Sholahuddin Al Ayyubi (Yayasan Al'Adzkiya Rantauprapat, 2025)
Early marriage has become a complex social issue in various regions of Indonesia, including Padang Hulu Subdistrict, Tebing Tinggi. The Ministry of Religious Affairs of Tebing Tinggi has taken initiatives to reduce the prevalence of early marriage through various programs and communication activities. The Ministry of Religious Affairs in Padang Hulu plays an essential role in preventing the community from engaging in early marriage. This study aims to explore the communication strategies of the Ministry of Religious Affairs of Tebing Tinggi in preventing early marriage in Padang Hulu Subdistrict. The research method employed is descriptive analysis with a qualitative approach, which seeks to describe and explain actual conditions based on factual evidence. Data were collected through interviews with four respondents, consisting of the head of the Ministry of Religious Affairs, members of the institution, and two community members. The Ministry has implemented several efforts to prevent early marriage, including outreach to community leaders, subdistrict officials, and neighborhood heads. Programs initiated by the Ministry include the Sakinah Family Counseling Program and the selection of religious cadres, which are expected to discourage early marriage practices among the community. The findings of this research show that the Ministry of Religious Affairs of Tebing Tinggi applies an informative communication strategy aimed at influencing the public by providing enlightenment and awareness.